The Mechanics of Mitotic Cell Rounding - Taubenberger, Anna V.; Baum, Buzz; Matthews, Helen K. (Frontiers in Cell and Developmental Biology, 2020)
When animal cells enter mitosis, they round up to become spherical. This shape change is accompanied by changes in mechanical properties. Multiple studies using different measurement methods have revealed that cell surface tension, intracellular pressure and cortical rigidity increase upon entry into mitosis. These cell-scale, biophysical changes are driven by alterations in the composition and architecture of the contractile acto-myosin cortex, and osmotic swelling and enable a cell to exert force against the environment in mitosis. Limiting the ability of cells to apply a rounding force, for example using confinement, leads to severe defects in spindle assembly and cell division. This requirement to push against the environment to create space for spindle formation is likely to be of even greater importance for cells dividing in tissues, yet there is a relative paucity of measurements of mitotic mechanics in vivo. Here we summarize the evidence and the tools used to show that cells exert a rounding force in mitosis, review the molecular basis for this force generation and discuss its function for ensuring successful cell division in single cells and for cells dividing in normal or diseased tissues.